Implementation of rapid application development for spatio-temporal database management - Yerik Afrianto Singgalen (Institute of Computer Science (IOCS), 2024)
This study aims to investigate the application of Rapid Application Development (RAD) in developing a spatio-temporal database management system, focusing on a case study in North Halmahera Regency. The primary objective is to assess the effectiveness of RAD in expediting the development process and enhancing the adaptability of the system to the dynamic spatial data requirements in the region. The methodology involves iterative development cycles, encompassing requirements planning, user design, construction, and cutover phases. The results demonstrate the successful implementation of RAD principles, showcasing accelerated development timelines and flexibility in accommodating changes. The system, tailored to the specific needs of North Halmahera, proves to be a valuable tool for urban planning, land management, and decision-making. In conclusion, using RAD to develop the spatio-temporal database management system presents a promising approach for swiftly adapting to evolving spatial data demands, ultimately contributing to more effective and responsive governance in North Halmahera Regency